2019
DOI: 10.1158/1078-0432.ccr-18-0284
|View full text |Cite
|
Sign up to set email alerts
|

Combined CDK4/6 and Pan-mTOR Inhibition Is Synergistic Against Intrahepatic Cholangiocarcinoma

Abstract: Intrahepatic cholangiocarcinoma (ICC) is an aggressive cancer type, lacking effective therapies and associated with a dismal prognosis. Palbociclib is a selective CDK4/6 inhibitor, which has been shown to suppress cell proliferation in many experimental cancer models. Recently, we demonstrated that pan-mTOR inhibitors, such as MLN0128, effectively induce apoptosis, although have limited efficacy in restraining proliferation of ICC cells. Here, we tested the hypothesis that palbociclib, due to its antproliferat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 41 publications
2
42
0
Order By: Relevance
“…These findings shed further light on the cell cycle-dependent phosphorylation of 4E-BP1, the regulation of which was previously reported to be mediated by CDK1 and CDK12 in mitotic cells [29,61,62], and PLK1 and CDK1 in cells undergoing meiosis [22,32,[63][64][65]. Given this newly discovered role of CDK4, it is likely that inhibition of mitotic 4E-BP1 phosphorylation is a previously unknown function of CDK4/6 inhibitors such as palbociclib, and may explain the synergy between these drugs and mTOR inhibitors [66][67][68][69][70][71][72]. It is important to try to reconcile these observations with those previously observed that report CDK1 as the principal kinase that phosphorylates 4E-BP1 during mitosis [30,33].…”
Section: Resultsmentioning
confidence: 77%
“…These findings shed further light on the cell cycle-dependent phosphorylation of 4E-BP1, the regulation of which was previously reported to be mediated by CDK1 and CDK12 in mitotic cells [29,61,62], and PLK1 and CDK1 in cells undergoing meiosis [22,32,[63][64][65]. Given this newly discovered role of CDK4, it is likely that inhibition of mitotic 4E-BP1 phosphorylation is a previously unknown function of CDK4/6 inhibitors such as palbociclib, and may explain the synergy between these drugs and mTOR inhibitors [66][67][68][69][70][71][72]. It is important to try to reconcile these observations with those previously observed that report CDK1 as the principal kinase that phosphorylates 4E-BP1 during mitosis [30,33].…”
Section: Resultsmentioning
confidence: 77%
“…Previous studies have revealed that PI3K/AKT, CCND1/CDK6 and MAPK pathways play key role in developing CCA [37][38][39][40]. For example, Wang et al, clari ed that TSPAN1 was involved in CCA progression via PI3K/AKT pathway [41].…”
Section: Discussionmentioning
confidence: 99%
“…The mTOR pathway regulates energy homeostasis and engages in cancer cell survival in cellular metabolic stress such as depletion in nutrients and energy (23,24). The downregulation of mTOR pathway signaling reduces cancer growth and has therapeutic potential for CCA (61)(62)(63)(64). CCA cells which need OXPHOS for energy requirements can be targeted by impairing mitochondrial energy metabolism.…”
Section: Therapeutic Interventions Related To Reprogrammed Metabolismmentioning
confidence: 99%